Lean Healthcare in A Brazilian Hospital: Application of the Ishikawa Diagram in the Processes Management of an Operating Theater - Fraga Vilela, Flavio; Wong, Kam Cheong; Miranda Bócoli, Guilherme; Silva Junho , Maria Fernanda; Nunes Lima Dias, Mariana; Custodio Zampollo, Poliana; de Carvalho Machado , Lucas Henrique (International Journal of Innovative Research in Medical Science, 2023)
Patient safety has been gaining prominence since the beginning of the 20th century, as it is a fundamental component of quality in health. This way, the application of Lean Healthcare (LH) can offer patient-focused care, achieving better results for patients, institutional management, operational management, greater customer and employee satisfaction. In this context, the present study aims to apply the LH, through the Ishikawa Diagram, to look for the possible causes of delays in surgical procedures in a regional hospital. The research used a cross-sectional, retrospective and quantitative study to survey the prevalence and nature of errors and their causes. After that, visits were made to the surgical center to explain the application of Ishikawa Diagram and its practical importance. Then, using the Ishikawa Diagram tool, the professionals were asked about the possible causes of the situation presented, participating in the elaboration of cause-effect diagrams together with the researchers through the use of a digital technology conceived in VBA (Visual Basic Application). After analysing 32 surgical procedures, four root main causes and twelve specific causes were identified for the delays in the surgical procedure. Workforce is the main cause of delays in the operating room (51%), followed by methods (22%). These causes resulted in financial losses for the hospital. However, these causes could be identified and prevented.